2021
DOI: 10.1111/mcn.13153
|View full text |Cite
|
Sign up to set email alerts
|

The quality of maternal nutrition and infant feeding counselling during antenatal care in South Asia

Abstract: Antenatal care (ANC) provides a platform to counsel pregnant women on maternal nutrition and to prepare the mother to breastfeed. Recent reviews suggest that gaps in the coverage and quality of counselling during pregnancy may partly explain why services do not consistently translate to improved behavioural outcomes in South Asia. This scoping literature review collates evidence on the coverage and quality of counselling on maternal nutrition and infant feeding during ANC in five South Asian countries and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Our study identified substantial data gaps on coverage and quality of maternal nutrition services, which is consistent with previous findings in the Asia region (Torlesse et al, 2021). National surveys and routine monitoring data systems lacked process indicators needed for tracking nutrition interventions in ANC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study identified substantial data gaps on coverage and quality of maternal nutrition services, which is consistent with previous findings in the Asia region (Torlesse et al, 2021). National surveys and routine monitoring data systems lacked process indicators needed for tracking nutrition interventions in ANC.…”
Section: Discussionsupporting
confidence: 92%
“…Before the publication of the WHO ANC guidelines in 2016, nutrition interventions received little priority in ANC services. Thus, there is scarce evidence on the content, quality, and factors associated with maternal nutrition interventions (MNIs) during ANC (Benova et al, 2018; Torlesse et al, 2021), other than IFA supplementation (Kavle & Landry, 2018; Sanghvi et al, 2010; Sununtnasuk et al, 2016). This paper provides details on the package of four MNIs as part of ANC in two sub‐Saharan and two South Asian countries (Bangladesh, Burkina Faso, Ethiopia and India).…”
Section: Introductionmentioning
confidence: 99%
“…A recent evidence review on maternal nutrition counseling has highlighted concerns of lack of information related to the coverage and quality of counseling, specifically the format, duration, and frequency of counseling; content of health worker training; and supportive supervision ( 11 ). Our study bridged key evidence gaps by including details of timing and frequency of contacts by service providers, duration and content of counseling, and mode of interactions through home visits and community events.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal nutrition interventions can be delivered through several platforms; among them, health systems are considered the most effective platform to reach women and children in the first 1000 d ( 10 ). Gaps in coverage and inconsistent quality of counseling on maternal nutrition, however, have hindered the improvement of behavioral outcomes associated with the services ( 11 ). In 2016, the WHO issued new guidelines on antenatal care (ANC) for a positive pregnancy experience ( 12 ), but evidence-based interventions to improve maternal nutrition are currently poorly integrated in ANC services globally ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Asian countries. 31 We did not measure the quality of the counselling messaging themselves, only their delivery. However, Torlesse et al's findings may mean that the coverage measures in our population may overestimate the proportion of women who received quality counselling that led to information transfer from provider to client.…”
Section: Discussionmentioning
confidence: 99%